KLF9 in cancer: a potential prognostic marker and therapeutic target - Xiao, Xiaoxiao; Dai, Zhipeng; Liu, Fang; Zhao, Xingqi; Wu, Qiang (Frontiers in Oncology, 2025)
Kruppel-like factor 9 (KLF9) is a transcription factor that has gained significant attention in recent years for its critical involvement in development and progression of various cancers. Recent research has revealed the dual nature in tumorigenesis, where KLF9 can function as either a tumor suppressor or an oncogene, depending on the cellular context. Clinically, KLF9 emerges as a potential prognostic biomarker due to its differential expression patterns across various cancer types, with lower KLF9 levels often correlating with poorer patient outcomes. Furthermore, KLF9 represents a promising therapeutic target, as modulating its activity may offer new strategies for cancer treatment. Overall, the present review provides new insights and perspectives for future research on KLF9 in cancer, underscoring its importance in personalized medicine.